Activation Induced Deaminase and Tumor Progression in Chronic Lymphocytic Leukemia - (:unkn) unknown (My University, 2025)
Chronic Lymphocytic Leukemia (CLL) is as a monoclonal expansion of more than 5,000 mature CD5-expressing B cells per µL of peripheral blood. CLL is the most frequent leukemia worldwide and since its incidence dramatically increases with age, it represents a serious challenge to aging countries. CLL is characterized by the proliferation and accumulation of the clonal cells within the blood, bone marrow, lymph nodes, and spleen. This disease is heterogeneous in terms of genetics, biologic behavior, and clinical outcome. Many cases are detected during a routine complete blood count followed by specialized assessment of such asymptomatic lymphocytosis by flow cytometry. Whereas some patients might remain asymptomatic during long periods of time without the need of immediate treatment, others develop an aggressive disease often requiring several courses of chemoimmunotherapy. Despite recent progress in understanding leukemogenesis and the development of novel treatments, CLL remains incurable. Novel treatments such as B-Cell receptor signaling inhibitors (ibrutinib, acalabrutinib) or BCL-2 inhibitors (venetoclax) induce encouraging remission rates and show a better toxicity profile as compared to standard chemoimmunotherapy. These advances have imposed new challenges, such as the reborn interest in identifying patients at higher risk of progression and therefore more likely to benefit from early interventions. We have recently demonstrated that the overexpression of the mutagenic enzyme activation induced deaminase (AID), induces mutations that promote tumor progression and a more aggressive disease in vivo. Therefore, we hypothesize that the detection of AID expression might allow prognostic stratification of patients diagnosed with CLL, helping to identify patients more likely to need treatment. In addition, the molecular characterization of AID-overexpressing tumor cells will also help to understand molecular pathways involved in disease progression. The main goal of this proposal is to evaluate the clinical significance of AID expression and the role of AID-induced mutagenesis in CLL progression. Our specific goals are: 1. To analyze AID expression in a cohort of CLL patients 2. To perform a molecular characterization of AID overexpressing tumors 3. To establish the frequency of recurrent AID-induced mutations